Risk assessment for screening of diabetes mellitus among first year pharmacy students - Burhan, Siti Aisyah; Soe, May Khin Soe (2019)
Introduction: The prevalence of Type 2 diabetes among young-age group rose 30 percent nowadays although Type 2 diabetes used to be called adult-onset. Objectives: This cross-sectional study aimed to assess T2DM risk among first year pharmacy students of IIUM. Material and Method: Finnish Diabetes Risk Assessment was used to study the diabetes risk factors together with laboratory test of random plasma glucose (RPG). The randomized stratified cluster sample of first year pharmacy students (n=106) was recruited in this practical-based survey. Result: Among 39 male and 68 female, 62.2% (n= 66) of the sample population both gender were found having slightly elevated risk for T2DM, 10.3% (n=11) were moderately risk and only 6.6% (n=7) were at high risk. The diabetes risk ranged from 3 to 18 with the mean score of 8.93 ± 2.9. Moreover, positive correlation was found between RPG and the total risk scores which emphasized that exposure with high blood sugar level lead to a high risk of diabetes. Likewise, students with family history of diabetes have high tendency to develop T2DM that was highlighted in this study. Based on the BMI, 79.4% (n=85) of total students have desirable weight while the remaining 15.9% (n= 17) and 4.7% (n= 5) was found to be overweight and obese respectively. The mean RBG of all students was 5.43 mmol/l and RBG value of 16% (n=17) of total students were observed in approaching to prediabetes value. Conclusion: Most of students have elevated risk factor of diabetes; therefore, early intervention should be initiated to prevent the prevalence of T2DM.